APSIPA transactions on signal and information processing (Cambridge)
Asia-Pacific Signal and Information Processing Association (APSIPA) serves as an international forum for signal and information processing researchers across a broad spectrum of research, ranging from traditional modalities of signal processing to emerging areas where either (i) processing reaches higher semantic levels (e.g., from speech recognition to multimodal human behaviour recognition) or (ii) processing is meant to extract information from datasets that are not traditionally considered signals (e.g., mining of Internet or sensor information).
Keywords: Engineering